Analysis of Variability for Qualitative and Quantitative Traits in Coleus forskohlii Briq. - Kavitha, C; Vadivel, E; Rajamani, K; Thangamani, C (Journal of Horticultural Sciences, 2007)
Thirty seven Coleus forskohlii genotypes collected from different regions of Tamil Nadu and Karnataka were subjected to diversity analysis based on NBPGR descriptors. Eleven qualitative and fourteen quantitative traits of C. forskohlii were evaluated to assess the morphological variations available among the collected genotypes. For qualitative traits, a large number of genotypes out of 37 clustered together at 74 % similarity in four different groups. The dendrogram contract based on fourteen quantitative traits for the same set of genotypes did not reveal a clear pattern in grouping and the genotypes were grouped into ten different clusters. Cluster analysis of various sets of data revealed different groups of genotypes for each of the data set. A poor congruence observed among data sets of qualitative and quantitative traits in the comparison indicated that the morphological traits are not suitable for precise discrimination of closely related genotypes in C. forskohlii.